The Progression of Medical Innovations, Challenges, and Implications on Human Health Associated with Nanoparticles - Mude, Gaurav S. (Asian Journal of Pharmaceutics (AJP), 2024)
Nanoparticles (NPs) have emerged as versatile tools in the field of medicine, presenting promising prospects for drug delivery and diagnostics. Their distinctive attributes, including a high surface mass ratio and ability to transport substances, facilitate precise drug targeting, minimize toxicity, and enhance therapeutic effects. Despite these advantages, the rapid progress of nanotechnology in medicine introduces challenges that necessitate rigorous toxicological assessments to ensure safe application. Researchers are actively bridging the divide between the risks associated with combustion-derived NPs and the potential benefits of engineered NPs in medical contexts. A comprehensive exploration of their impact on the cardiovascular and neurological systems offers insights into their behavior and paves the way for responsible practices in nanomedicine. Unlocking the full capabilities of nanotechnology calls for collaborative endeavors between particle toxicologists and drug delivery specialists, unraveling the intricacies of NP-cell interactions, and revolutionizing drug administration to elevate health-care outcomes.